Le portrait de la monomanie : rencontres de subjectivités - Jubinville, Ginette (RACAR : Revue d'art canadienne / Canadian Art Review, 2011)
This article considers the possible influences of the physiognomic studies on the Romantic portrait, using as paradigms Géricault’s Portraits de Monomanes. Painted during the period of the very beginning of French psychiatry, at a time when this new discipline began to recognize the presence of the subject in the madman, these works question the dialogue engaged between art and psychiatry, between insanity and reason, between the visibility and invisibility of madness on human features. In considering this crossed gaze on the insane thus engendered, this article delves specifically into two facets of this duality. First, it examines the development of medico-legal psychiatry, in favour of which the alienist Jean-Étienne Georget—presumed owner of the Monomanes—had actively worked in an effort to impose his discipline as the only one able to recognize the invisible marks of mental illness. Second, it considers a series of works commissioned by the alienist Jean-Étienne-Dominique Esquirol from two artists: Georges-François-Marie Gabriel and Ambroise Tardieu. It is argued that these works, as for Géricault’s Monomanes, individualize the insane in the early nineteenth century and acquire a characteristic specific to the genre of portraiture: recognition and commemoration of a subject.